Does prenatal care reduce the risk of complications of labor and delivery among urban poor women in Metro Manila, Cebu and Cagayan De Oro, the Philippines? - Sodara, Chan
The objective of this study was to ascertain the role of prenatal care in reducing the risk of complications of labor/delivery and comparing by how much the risk of complications would be reduce among women who had prenatal care to those who had no prenatal care.A retrospective cohort of 699 women who had full term delivery during the period 1 January to 31 December 1994, in urban poor areas of Metro Manila, Metro Cebu and Cagayan de Oro, Philippines, was studied. The data were derived from the results of Urban Health and Nutrition Project, 1995.The incidence of complications of labor/delivery was 41.7regardless of the kind complications. The most frequent complications were prolonged labor (22.7) and premature rupture of the membrane (13.4).The study found no difference in risk of complications of labor/delivery according to the frequency of prenatal vistis. Women with 1-7 prenatal visits and women with more than 7 visits experienced more or less the same incidence of complications.The risk of complications of labor/delivery may be reduced by 50to 80if young mothers, regardless of gravidity attended prenatal care.More in-depth and informative researches are recommended to clarify the effect of prenatal care on complications of labor/delivery.